Le surplus et son importance pour une compagnie d’assurance-vie - Ross, Jacques (Assurances, 1981)
The surplus in life insurance is an extremely important item of the balance sheet. It is formed of paid-up capital and funds accumulated in the company throughout the years as an additional security for the insureds. The surplus must be followed very closely in periods of inflation, as it represents an indispensable security for the operations of the company.